2020
DOI: 10.7759/cureus.10995
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Bacterial Peritonitis in Cardiogenic Ascites

Abstract: The most common cause of ascites is liver cirrhosis. Additional causes such as heart failure, cancer, and pancreatitis among others can also precipitate this abnormality. Spontaneous bacterial peritonitis (SBP) is an infection of ascitic fluid that happens without any evidence of an intra-abdominal surgically-treatable cause. Ascites of cardiac origin can also be complicated by SBP. Here we present a case of a 62-year-old male with extensive cardiac history who presented to our service with ongoing dyspnea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, in the present case, SBP developed despite the absence of cirrhosis. Some reports have suggested that cardiogenic ascites with heart failure due to any type of heart disease (e.g., CP, ischemic heart disease, congenital heart disease, valvular heart disease, or arrhythmia) may be a possible cause of SBP, even in the absence of cirrhosis ( 5 , 7 - 10 ). In patients with heart failure, substantial hemodynamic changes, such as hypoperfusion and congestion in the intestines, can alter the gut morphology, permeability, and function and induce the growth of microbiota that may ultimately stimulate bacterial translocation and endotoxin release ( 5 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present case, SBP developed despite the absence of cirrhosis. Some reports have suggested that cardiogenic ascites with heart failure due to any type of heart disease (e.g., CP, ischemic heart disease, congenital heart disease, valvular heart disease, or arrhythmia) may be a possible cause of SBP, even in the absence of cirrhosis ( 5 , 7 - 10 ). In patients with heart failure, substantial hemodynamic changes, such as hypoperfusion and congestion in the intestines, can alter the gut morphology, permeability, and function and induce the growth of microbiota that may ultimately stimulate bacterial translocation and endotoxin release ( 5 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac ascites, one of the classical right-sided heart failure (HF) findings mainly caused by tricuspid valve disease and constrictive pericarditis, only contributes to 5% of all ascites cases. 1 Although treatments with diuretics and nutritional therapy with sodium restriction are effective in controlling ascites, massive cardiac ascites observed in advanced HF is sometimes refractory to such non-invasive conventional therapies. Drainage of refractory cardiac ascites by abdominal paracentesis is an invasive conventional therapy that can alleviate patients’ symptoms; however, it often facilitates hypoproteinaemia due to protein loss, leading to malnutrition and renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%